2015
DOI: 10.3389/fpsyg.2015.00956
|View full text |Cite
|
Sign up to set email alerts
|

Executive and semantic processes in reappraisal of negative stimuli: insights from a meta-analysis of neuroimaging studies

Abstract: Neuroimaging investigations have identified the neural correlates of reappraisal in executive areas. These findings have been interpreted as evidence for recruitment of controlled processes, at the expense of automatic processes when responding to emotional stimuli. However, activation of semantic areas has also been reported. The aim of the present work was to address the issue of the importance of semantic areas in emotion regulation by comparing recruitment of executive and semantic neural substrates in stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 83 publications
13
93
1
Order By: Relevance
“…As it is apparent from Fig. 2, tasks of explicit emotion regulation recruit not only the dorsal prefrontal areas that are typically associated with executive function, but also the temporal and parietal lobes (Messina, Bianco, Sambin, & Viviani, 2015). These findings, which are not predicted by dual-process models of emotion regulation, suggest the involvement of areas of the semantic system in effortful regulation.…”
Section: Implicit Emotion Regulationmentioning
confidence: 82%
“…As it is apparent from Fig. 2, tasks of explicit emotion regulation recruit not only the dorsal prefrontal areas that are typically associated with executive function, but also the temporal and parietal lobes (Messina, Bianco, Sambin, & Viviani, 2015). These findings, which are not predicted by dual-process models of emotion regulation, suggest the involvement of areas of the semantic system in effortful regulation.…”
Section: Implicit Emotion Regulationmentioning
confidence: 82%
“…In the present study, we demonstrated lower activation within the medial prefrontal cortex during high WM load in mTBI patients compared to healthy controls. This region is important with respect to executive functioning, but also with regard to emotion regulation (Euston et al 2012; Messina et al 2015). Furthermore, the medial prefrontal cortex is a core area of the DMN and an important relay station in the interaction between the DMN and other (executive) brain networks (Buckner et al 2008; Seeley et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of work has focused on the neural underpinnings of reappraisal, most commonly using experimental designs in which participants are asked to view emotionally-relevant stimuli and to engage in emotion regulation or as a control condition, to simply view the stimulus. In a meta-analysis of 48 studies, reappraisal was consistently associated the frontoparietal network, including activation of the lateral prefrontal cortex (LPFC), dorsal anterior cingulate cortex (dACC), and the intraparietal sulcus (IPS), and deactivation of the amygdala (Buhle et al, 2014; Messina, Bianco, Sambin, & Viviani, 2015). Emotion distancing, a form of reappraisal in which people try to distance themselves from negative emotions by thinking of the stimulus as far away, long ago, or less relevant to them, also has been found across seven studies to activate the frontoparietal network (Belden, Pagliaccio, Murphy, Luby, & Barch, 2015; Lewis, Todd, & Honsberger, 2007).…”
Section: Links Between Cognition and Emotionmentioning
confidence: 99%